AB0828-HPR Psychological and sexual disorders in patients with rheumatoid arthritis and correlation with disease activity. (23rd January 2014) - Villarreal, L.; Sandoval, C.; Real, A. P.; Boon, P.; Palomino, A.; Bello, J.; Santos-Moreno, P.
Abstract : Background: Emotional stability and sexual life are important dimensions of personality, therefore any involvement in these areas should be considered as important. Psychological and sexual disorders in rheumatoid arthritis (RA) are poorly described in literature. Objectives: The aim of this study was to describe psychological and sexual disturbances using CIE-10 and DSM-IV in patiens with RA and a possible correlation with disease activity. Methods: A descriptive study was performed in a specialized clinic dedicated to care patients with RA. 311 RA patients were included in the study, which were seen by the area of psychology, which information was collected through semi-structured interviews and non-probability sampling, also using classificatory criteria of pathologies described in two diagnostic manuals: DSM IV and CIE 10, applying descriptive epidemiology for continuous variables, measure of central tendency and dispersion for qualitative and categorical variables through percentages and averages; also Kruskall-Wallis`s statistics for bivariated analysis. Results: Total sample of patients was 311, 262 (84.2%) were women and 49 (15.8%) were men. Patients had a DAS28-3.41 ± 0.94 in average, a HAQ-0.41 ± 0.48, a medium age 58.1 ± 10.3 y/o; Using CIE-10 were found: 43.7% of patients had mixed disorder/disorder of mood in relation to disease (depressiveepisodeunspecified, depression and or anxiety), 19.2% had somatomorphic disorder, 4.2% unspecified disorder of eating behavior, 9.0% diagnosed sleep disorder and 18.6% no report disorders previously. It was not established correlation between type of psychological disorder and disease activity. Regarding sexual disorders were found: 47.5% reported no sexual activity, while 52.5% report sexual activity. Of these, 10.2% reported satisfactory sexual activity, 8.2 reported unspecified unsatisfactory sexual activity, 9.6% reported lack of sexual desire, 17.6% reported dyspareunia, 3.2% premature ejaculation, 3.5% orgasmic dysfunction. It was not established a correlation between level of sexual activity and disease activity using DAS28. Conclusions: According to these findings men and women have many psychological disorders in relation to RA; in both there is a prevalence of depressiveepisodeunspecified and depression/anxiety. On the other hand men and women have a high percentage of sexual disturbances in relation to RA. Disclosure of Interest: None Declared